2014
DOI: 10.3892/mmr.2014.2584
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the effects of gemcitabine against pancreatic cancer by oridonin via the mitochondrial caspase-dependent signaling pathway

Abstract: Gemcitabine is a first‑line chemotherapeutic agent used in the treatment of pancreatic cancer; however resistance of the disease to the drug often develops over time. Agents that can either enhance the effects of gemcitabine, or help to overcome the chemoresistance to the drug are needed for the successful treatment of pancreatic cancer. Oridonin is one such agent which is safe and multi‑targeted and has previously been shown to induce apoptosis in other tumor cells, through mitochondrial signaling pathways. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 32 publications
2
17
0
Order By: Relevance
“…ORI has been used as a drug for antitumor, anti-microbial, anti-inflammatory and antioxidant for many years (18). It has been reported that ORI can inhibit proliferation and induce apoptosis in various cancer cells, such as breast, pancreatic, lung, gastric and prostate cancer (8,(19)(20)(21)(22)(23), as well as induce apoptosis and senescence in colon cancer cells (12,24). Our data also confirmed that ORI can inhibit proliferation and induce apoptosis in HCT116 cells concentration-dependently, as well as inhibit the tumor growth of colon cancer.…”
Section: Discussionmentioning
confidence: 99%
“…ORI has been used as a drug for antitumor, anti-microbial, anti-inflammatory and antioxidant for many years (18). It has been reported that ORI can inhibit proliferation and induce apoptosis in various cancer cells, such as breast, pancreatic, lung, gastric and prostate cancer (8,(19)(20)(21)(22)(23), as well as induce apoptosis and senescence in colon cancer cells (12,24). Our data also confirmed that ORI can inhibit proliferation and induce apoptosis in HCT116 cells concentration-dependently, as well as inhibit the tumor growth of colon cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Oridonin also synergistically increased the cytotoxicity of Nutlin-3 [an inhibitor of murine double minute 2 (Mdm2)] against wild-type p53 osteosarcoma U2OS cells by enhancing cellular apoptosis via increasing the level of proapoptotic factor Bim and decreasing the levels of antiapoptotic factors Bcl-2 and Bcl-xl (Wang X. H. et al, 2017). Furthermore, oridonin also significantly increased the cytotoxicity and/or reversed drug resistance of various anticancer drugs such as cisplatin, gemcitabine, and lentinan by downregulation of Bcl2 expression and upregulation of Bax expression in multiple human cancer cell lines including ovarian, pancreatic, and liver cancers (Liu D. L. et al, 2014; Ma et al, 2016; Xu T. et al, 2017).…”
Section: Anticancer Tcms Through Affecting the Bcl-2/bax Pathwaymentioning
confidence: 99%
“…Human β-actin was chosen as the active control. The expression of various genes was measured by qRT-PCR as described previously [36][37][38][39][40][41][42][43]. On completion of PCR, products of each gene processed were separated by means of an electric field at 100 V and size on 1.5% agarose gels in 1 × TAE buffer, stained with ethidium bromide.…”
Section: C-dna Synthesis (Semi-quantitative Rt-pcr)mentioning
confidence: 99%